Exploring Determinants to Explain Aspects of Individual Investors’ Financial Behaviour - Salam Abdallah; Khalil Hilu (Australasian Accounting, Business and Finance Journal, 2015)
This study uses exploratory factor analysis and structural modelling to determine individual determinants that are likely to influence financial trading behaviour. A questionnaire was collected form 179 individual investors who traded in the United Arab Emirates. The study has determined three likely independent variables; namely, investors’ perception of information asymmetry, market perceptions and overconfidence, that may predict investor’s risk attitude. The findings are congruent with existing literature in this field, and add knowledge to the relatively new field of financial behaviour. These ﬁndings may provide valuable guidance for researchers and practitioners in understanding what may influence the risk attitude of investors and to explain possible reasons for inefficiencies of markets. Additionally, the study demonstrates the relevance of using structural modelling for understanding relationships between factors influencing financial behaviours, and in developing a behavioural framework.
Keywords: Impression Management; Narrative Disclosure; Chairman’s Statement; United Arab Emirates